(untitled) (Analysis in Theory and Applications, 2020)
Let A be a general expansive matrix on R^n. The aims of this article are twofold. The first one is to give a survey on the recent developments of anisotropic Hardy-type function spaces on R^n, including anisotropic Hardy–Lorentz spaces, anisotropic variable Hardy spaces and anisotropic variable Hardy–Lorentz spaces as well as anisotropic Musielak–Orlicz Hardy spaces. The second one is to correct some errors and seal some gaps existing in the known articles. Some unsolved problems are also presented.